Nivel de conocimiento sobre el cáncer cervical y el Papanicolaou en relación al temor, estrés o vergüenza al tamizaje: Un estudio transversal en una comunidad pobre de Lima - Castro, Miriam (2015)
OBJETIVE: To evaluate the association between the level of knowledge about cervical cancer and Pap smear (Pap) with fear, stress or embarrassment associated with this screening. DESIGN: Cross-sectional, prospective descriptive study based on community. MATERIALS AND METHODS: Using random cluster sampling, women in a poor community of Lima met, assessing their level of knowledge about cervical cancer and Pap smears and their perception of this screening. Chi square, odds ratios, confidence intervals were 95% and used logistic regression to assess the association study. RESULTS: Of 300 women between 18 and 50 years, 20% had their last Pap over two years and 20% had never done; 57 (19%) women reported having much fear, stress or embarrassment to screening, which was associated with being a teenager (OR 5.5, 95% CI 1.8 to 16.9), have five or less years of living in Lima from having llgado of the country (OR 2.6, 95% CI 1.3 to 5.2), not having had a sexual partner in the last year (OR 2.1, 95% CI 1.1-7.6) no previous pregnancies (OR 3.1, 95% CI 1.2-8.0), no prior Pap (OR4,7, IC9S 1.9 to 8.7%) and low knowledge about or regular Pap or cervical (OR4,1, 95% CI 2.2 to 7.9) cancer. In the multivariate analysis, the teenager be associated persisted and low or regular level of knowledge about the Pap and cervical cancer. CONCLUSION: It is recommended to inform the community about the Pap test for cervical cancer and improving negative attitudes associated with screening.